An assessment of the causes, cost effects and solutions to design-errorinduced variations on selected building projects in Nigeria - Dosumu, Oluwaseun; Aigbavboa, Clinton (University of the Free State, 2018)
Design errors and variations are inherently part of many construction projects and require deliberate effort to combat. The literature reviewed indicates that empirical studies of the cost effect of design-error-induced variations are scarce. This study investigates the causes of variation on building projects, the frequent design errors that lead to variation, the effects of design error on variation cost, and solutions to design-error-induced variation in design documents. A mixed methods research (interviews and 30 case study building projects) was used to collect the necessary data for the study. Interviews were conducted with 25 construction professionals to obtain information on the causes of variation on building projects and solutions to design-error-induced variation on building construction projects. Thirty documents including valuation breakdowns and variation/change order documents were obtained by convenience sampling technique and used for the extraction of design errors leading to variations and their associated costs. The data was analysed with frequencies and percentages. The study found that poor working drawing and lack of coordination among design documents are the major causes of variation. Errors in design calculations and wrong descriptions in specifications are prominent design errors that led to variation. Design errors account for roughly 36% of the variation cost of building projects. Structural and architectural drawings contain the largest number of errors among design documents, but electrical and mechanical documents have the highest contribution to variation cost. The study concluded that variation costs could be minimized if government policies, aimed at ensuring proper contract documentation, were put in place, and construction professionals were limited to their core roles on construction projects. Rechecking of design documents prior to use, knowledge sharing, and use of computer programs were among the recommended solutions to design-error-induced variation in project documents.

Ontwerpfoute en -variasies vorm inherent deel van baie konstruksieprojekte wat doelbewuste pogings verg om te bestry. Die literatuuroorsig dui daarop dat empiriese studies van die koste-effek van ontwerpfout-geïnduseerde variasie skaars is. Daarom ondersoek hierdie studie die oorsake van ontwerpfoutgeïnduseerde variasie, hul effekte op variasiekoste en oplossings vir ontwerpfoute in ontwerpdokumente. Die studie is uitgevoer op geselekteerde bouprojekte in Nigerië. Die gemengde metode van onderhoud- en 30 gevallestudie-bouprojekte is aangeneem in die versameling van die nodige data vir die studie. Onderhoud is met 25 konstruksiekenners gevoer om inligting te verkry oor die oorsake van variasie en oplossings om foute van boukonstruksieprojekte te ontwerp. Dertig dokumente wat insluit waardasieafbreekpunte en variasie-/veranderingsopdragdokumente is verkry deur die gemaksbepalingstegniek en gebruik vir die onttrekking van ontwerpfoute wat lei tot variasies en hul verwante koste. Die data is geanaliseer met frekwensies, somme en persentasies. Die studie het bevind dat swak werktekening en gebrek aan koördinasie onder ontwerpdokumente die hoofoorsake van variasie is. Foute in ontwerpberekeninge en verkeerde beskrywing in spesifikasies is die prominente ontwerpfoute wat tot variasie gelei het. Ontwerpfoute verteenwoordig tot 36% van die variasiekoste van bouprojekte. Strukturele en argitektoniese tekeninge bevat die meeste foute onder ontwerpdokumente, maar elektriese en meganiese dokumente maak die grootste bydrae tot variasiekoste. Die studie het tot die gevolgtrekking gekom dat variasiekoste in ’n groot mate tot ’n minimum beperk kan word indien regeringsbeleid om behoorlike kontrakdokumentasie te verseker, ingestel word en professionele persone beperk word om die werk van ander professionele persone te doen. Herontwerp van ontwerpdokumente voor gebruik, kennisdeling en gebruik van rekenaarprogramme is onder die aanbevole oplossings om foute van projekdokumente te ontwerp.
Keywords: Construction projects; Cost of error; Design documents; Design error; Variation cost; Valuation documents